Diseño y construcción de un deshidratador eléctrico automatizado para el secado de la semilla de cereales para el proceso de producción de harinas en agroindustrias - Herrera Jácome, José Ricardo (2015)
This investigative work was based on the need to design and build an electric dehydrator automated drying of grain seed, controlling the variables of time, temperature, through the programming of a control system that allows to be in line with the technological advances, the purpose is to improve the quality of the product and thus achieve optimize the time in the drying of seeds process taking into account the degree of humidity set by INIAP. The machine has an interface human machine (IHM) user which is programmed with various screens which are friendly: selecting method to use where we have the option of dehydration or drying, temperature range of different seeds information that help to use the different types of Andean seed, selection screen, sensors connections manual , modules of inputs and outputs of the PLC….